Potensi Salep Ekstrak Daun Sirih Merah Terhadap Profil Eritrogram Sebagai Terapi pada Luka Miasis (THE EFFECT OF RED BETEL LEAF EXTRACT OINTMENT IN ERYTHROGRAM PROFILES AS THERAPY IN MYASIS WOUND) - Widhyari, Sus Derthi; Wientarsih, Ietje; Mustika, Aulia Andi; Wardhana, April Hari; Darmakusuma, Dodi; Sutardi, Lina Noviyanti; Bintang, Muhammad (Jurnal Veteriner, 2018)
The objectives of this research was to examine the efficacy of red betel extract ointment to eritrogram profiles in infected sheep myiasis. Fifteen female sheeps were divided into five treatments, which were sheep without wound, treated with asuntol 2%, without any treatment,with red betel leaf extract ointment 2% and 4 %. Three incision wounds were made on the sheep’s back, 50 larvae given to every wounds to four treatment, except the healthy sheep (K). Blood was taken on the 0, 3th and 7th to determine erythrocytes counts, hematocrit values (PCV) and hemoglobin levels (Hb). The result showed that oitment of red betel leaf extract do not change the erythrogram profiles. The administration of red betel leaf extract ointment 4% has better eritrogram profiles than 2% Oitment of red betel leaf extract can be used as myasis therapy.
Keywords: darah, Chrysomya bezziana, domba garut, miasis